Influence of Far Infrared TiO2 and Multi-Walled Carbon Nanotubes Coatings on the Performance of a Hot Water Heater - Tun-Ping Teng; Shang-Pang Yu; Yeou-Feng Lue; Qi-Lin Xie; Hsiang-Kai Hsieh; Chia-Cing Huang (Applied Sciences, 2021)
This study selects titanium dioxide (TiO2) and multi-walled carbon nanotubes (MWCNTs) as far-infrared materials (FIRMs), and further adds water-based acrylic coatings to prepare far-infrared coatings (FIRCs). FIRCs are uniformly coated on #304 stainless steel sheets to make the test samples, which are then installed between the shell and insulation material of the hot water heater to measure the influences of various FIRCs on the performance of the hot water heater. The research results show no significant difference in the heating rate or heat insulation performance of the hot water heater with or without FIRCs coating. However, the uniformity of the water temperatures of the test samples is significantly improved with FIRCs. Considering that the uniformity of water temperature will inhibit the heating rate and heat insulation performance of the hot water heater, TiO2-FIRC should provide better performance improvement when applied to the hot water heater in this study. The application of TiO2-FIRC to large-scale hot water heaters with a high aspect ratio will effectively improve the quality of hot water supply in the future.